Middle school teachers’ perspectives of how service learning projects contribute to student well-being - Watt, Jennifer; Krepski, Heather; Heringer, Rebeca (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2024)
The purpose of this study was to explore how teacher practitioners in a Canadian middle school perceive students’ experiences of well-being in student-led service learning projects (SLPs). Through semistructured interviews, we explored five school practitioners’ accounts of how SLPs contributed to student relating and functioning in a well-being context. The themes identified demonstrate how well-being can be deliberately integrated within curricular aspects of schooling, and how student well-being can be enhanced as well as enriched when practitioners include well-being as an aim. We conclude that although students may encounter discomfort in the planning and implementation of SLPs, they provide authentic opportunities to develop student voice and autonomy, which can make education more meaningful to them.